-4(-5u+9)-5u=5(u-8)-2

Simple and best practice solution for -4(-5u+9)-5u=5(u-8)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-5u+9)-5u=5(u-8)-2 equation:



-4(-5u+9)-5u=5(u-8)-2
We move all terms to the left:
-4(-5u+9)-5u-(5(u-8)-2)=0
We add all the numbers together, and all the variables
-5u-4(-5u+9)-(5(u-8)-2)=0
We multiply parentheses
-5u+20u-(5(u-8)-2)-36=0
We calculate terms in parentheses: -(5(u-8)-2), so:
5(u-8)-2
We multiply parentheses
5u-40-2
We add all the numbers together, and all the variables
5u-42
Back to the equation:
-(5u-42)
We add all the numbers together, and all the variables
15u-(5u-42)-36=0
We get rid of parentheses
15u-5u+42-36=0
We add all the numbers together, and all the variables
10u+6=0
We move all terms containing u to the left, all other terms to the right
10u=-6
u=-6/10
u=-3/5

See similar equations:

| 11/4b=83/4 | | 33=-3v | | 71+y=90 | | 2^3x=2 | | 5y+30=-4 | | Y=20+(-12)x | | x+(-8)=18 | | 3y+5+73=180 | | 6/9x=-5/9 | | f−9.8​=9.5​ | | a^2-7a=a+20 | | 22+x=-12 | | x+70=x+20=x | | 85=5-8v | | (z/12)=(4/5) | | 15-4x+12=19 | | 6/8m=25 | | 3x-9x+44=2x+36 | | 5x-3+2×=10 | | A=6x5/2 | | 2×+6y=-19 | | 3(1)-2y=10 | | 148+2x=193-1 | | a2-7a=a+20 | | 4m/2=20 | | 2y=10+3(1) | | 6x+6=12x+6 | | (2x+52)=108 | | 3/4g=6/8 | | 2x+33=8x-9 | | 5n+06=2 | | 0.8(x600)=2,000 |

Equations solver categories